2019
DOI: 10.3221/igf-esis.49.52
|View full text |Cite
|
Sign up to set email alerts
|

Rock Brittleness Evaluation Method Based on the Complete Stress-Strain Curve

Abstract: Brittleness plays an important role in the brittle failure process of rocks, and is also one of the important mechanical properties of rocks and a key indicator in rock engineering such as hydraulic fracturing, tunnelling machine borehole drilling and rockburst prediction. Therefore, aiming at the applicability of the brittleness index, this paper summarizes and analyzes the existing brittleness indices based on different experimental methods. Through analysis, it is found that many of the existing methods hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The whitenization differential Equation (6) of the grey Verhulst model, which is the first-order differential equation, can be obtained from the x ð1Þ ðkÞ…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The whitenization differential Equation (6) of the grey Verhulst model, which is the first-order differential equation, can be obtained from the x ð1Þ ðkÞ…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, China's engineering construction has developed rapidly, especially for deep foundation pit projects, caused by the need of large-scale public facilities and lots of exploitation of underground spaces [1][2][3][4][5][6][7][8][9]. However, the settlement of the foundation pit is affected by many factors, such as the excavation rate, the real-time excavation depth, changes in groundwater level, internal friction angle, soil weight, and number of supports [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Brittleness is the key parameter describing the rock failure and is a fundamental parameter in various fields, e.g., mining engineering, rock mechanics, unconventional oil, and hydraulic fracturing [1][2][3][4][5][6][7][8][9][10]. Nowadays, the definition for rock brittleness is proposed in different engineering fields.…”
Section: Introductionmentioning
confidence: 99%
“…According to different research purposes, domestic and foreign scholars have proposed many indicators of rock brittleness according to the definition of brittleness and failure phenomena. Zhang et al (2020) have established a new brittleness evaluation index and revealed the evolution process of the overall fracture induced by the internal rock fracture, which is based on the energy mutation process of the quasistatic equilibrium equation of the two-body system [16]; Zhao and Guo (2020) have analyzed the failure characteristics of rocks from the energy point of view and established a brittleness evaluation method based on the relationship between fracture energy, mechanical parameters, and mineral composition [17]; have conducted experiments on two materials with different length-diameter ratios and found that the use of postpeak data is of great significance [18]; Zhou et al (2020) have analyzed the influence of unloading rate on rock mechanical parameters, failure characteristics, and brittleness, through axial loading and confining unloading experiments, and then proposed a brittleness evaluation method considering the unloading effect [19].…”
Section: Introductionmentioning
confidence: 99%